The Red Hills of Florida, 1528-1865 - Paisley, Clifton (Book collections on Project MUSE., 1989)
The Red Hills section of northern Florida is composed of Leon County, where Tallahassee is located, and its neighboring counties of Gadsden and Jackson to the west and Jefferson and Madison to the east. The land is distinctive band of rolling red clay hills that extends for 150 miles along the border of Alabama and Georgia. This well-written narrative chronicles the history of the region from the time of first European contact in 1528 through the end of the Civil War, and provides a comprehensive study of this vital section of northern Florida. Recent excavation of t.